Impact of Zinc Nutrition on Growth and Yield of Sweet Basil (Ocimum basilicum) - Bhagya, Laxmi K.; Dutta, Babli; Medda, P. S.; Maitra, Soumen; Sinha, A. K. (International Journal of Economic Plants, 2025)
The present experiment was done during May, 2022 to February, 2023 at the Departmental plot of Plantation Crops and Processing, Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India. Seeds of Ocimum basilicum variety CIM-Saumya were collected from the Central Institute of Medicinal and Aromatic Plants, Lucknow. The experiment was done to study the performance of sweet basil (Ocimum basilicum) under varying levels of zinc. Zinc is an important micronutrient associated with several enzymatic activities in all photosynthetic plants. The design of the experiment followed was randomized block design with seven treatments and three replications. The treatment details are as follows: T1=Control (FYM @ 10 t ha-1), T2=Recommended dose of fertilizer (FYM @ 10 t ha-1 with N:P:K 120:100:100 kg ha-1), T3= RDF+Zn @ 0.25%, T4=RDF+Zn @ 0.50%, T5=RDF+Zn @ 0.75%, T6=RDF+Zn @ 1.0%, T7=RDF+Zn @ 1.25%. The maximum plant height (114.66 cm), number of primary branches (16.43) and secondary branches (85.07), and plant spread (1911 cm2) was recorded when treated with RDF+Zn @ 0.75% whereas the highest plant girth (1.29 cm) obtained in RDF+Zn @0.50%. Yield parameters like number of leaves found maximum with RDF+Zn @ 0.75% at 30, 60 and 90 days interval respectively. Fresh and dry herbage yield was also found highest in RDF+Zn @ 0.75% (32.5 t ha-1). The results of the experiment showed that application of recommended dose of fertilizers with zinc increased both vegetative growth as well as herbage yield of Ocimum basilicum under Terai zone of West Bengal.